2005
DOI: 10.1103/physrevlett.95.256401
|View full text |Cite
|
Sign up to set email alerts
|

Polaronic Quasiparticles in a Strongly Correlated Electron Band

Abstract: We show that a strongly renormalized band of polaronic quasiparticle excitations is induced at the Fermi level of an interacting many-electron system on increasing the coupling of the electrons to local phonons. We give results for the local density of states at zero temperature both for the electrons and phonons. The polaronic quasiparticles satisfy Luttinger's theorem for all regimes considered, and their dispersion shows a kink similar to that observed experimentally in copper oxides. We calculate the quasi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…In the limit of linear response the equilibrium value of the one-electron Green function can be used to evaluate (36), and the resulting expression for the differential conductance G = dI/dV through a quantum dot is…”
Section: B Application To Quantum Dotsmentioning
confidence: 99%
“…In the limit of linear response the equilibrium value of the one-electron Green function can be used to evaluate (36), and the resulting expression for the differential conductance G = dI/dV through a quantum dot is…”
Section: B Application To Quantum Dotsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] For the pure Holstein case, Freericks et al 7,8 found instabilities to charge order and superconductivity by quantum Monte Carlo ͑QMC͒ and iterated perturbation theory for different filling factors. At half-filling, Benedetti and Zeyher, 10 and Hague and D'Ambrumenil, 23 investigated the normal state and found a breakdown of Migdal-Eliashberg theory when a lattice instability develops for stronger electron-phonon coupling.…”
Section: Introductionmentioning
confidence: 99%
“…This means that the Mott insulator phase is robust against the deviation from the just half-filled condition in the presence of the finite electron-phonon interaction. Fruitful results at U ≈ S with rather small t (the lower-central area of the t-U-S triangle) have been expected near the half-filled condition [81][82][83], and more reliable calculations have been given by the dynamical mean-field theory [72,73,[87][88][89][90][91][92]. Large bipolarons at U ≈ S may play an important role in superconductivities [72,73,[87][88][89][90]92].…”
Section: T-u-s-n Diagrammentioning
confidence: 99%